A psicologia nos cuidados paliativos do paciente com câncer: um olhar fenomenológico - Mello, Gabriela Alves Byron de (Brasil, 2023)
Palliative Care can be understood as a multidisciplinary medical practice aimed at providing relief for patients from the stress and symptoms of a serious illness. It’s primary objective is to provide an active and complete care plan that seeks to offer patients, for whom curative treatment is no longer an option, a better quality of life. This article is a literature review that focuses on knowledge production from the last 5 years. From a phenomenological perspective, it aims to analyze the theoretical references in regards to the importance of the psychologist's role in the care of cancer patients in Palliative Care. The analysis shows that the literature exploring the importance of the psychologists role in the palliative care team is still scarce. That being said, it remains evident that psychological care greatly helps manage the suffering of the patient and his family.